Open questions on the mechanisms of neuromodulation with applied and endogenous electric fields - Marom Bikson (Frontiers Research Topics, 2015)
Despite increased knowledge, and more sophisticated experimental and modeling approaches, fundamental questions remain about how electricity can interact with ongoing brain function in information processing or as a medical intervention. Specifically, what biophysical and network mechanisms allow for weak electric fields to strongly influence neuronal activity and function? How can strong and weak fields induce meaningful changes in CNS function? How do abnormal endogenous electric fields contribute to pathophysiology? Topics included in the review range from the role of field effects in cortical oscillations, transcranial electrical stimulation, deep brain stimulation, modeling of field effects, and the role of field effects in neurological diseases such as epilepsy, hemifacial spasm, trigeminal neuralgia, and multiple sclerosis.